Unexpected Compensatory Increase in Shank3 Transcripts in Shank3 Knock-Out Mice Having Partial Deletions of Exons - Jin, Chunmei; Kang, Hyae Rim; Kang, Hyojin; Zhang, Yinhua; Lee, Yeunkum; Kim, Yoonhee; Han, Kihoon (Frontiers in Molecular Neuroscience, 2019)
Genetic variants of the SH3 and multiple ankyrin repeat domains 3 (SHANK3) gene, which encodes excitatory postsynaptic core scaffolds cause numerous brain disorders. Several lines of Shank3 knock-out (KO) mice with deletions of different Shank3 exons have previously been generated and characterized. The different Shank3 KO mouse lines have both common and line-specific phenotypes. Shank3 isoform diversity is considered a mechanism underlying phenotypic heterogeneity, and compensatory changes through regulation of Shank3 expression may contribute to this heterogeneity. However, whether such compensatory changes occur in Shank3 KO mouse lines has not been investigated in detail. Using previously reported RNA-sequencing analyses, we identified an unexpected increase in Shank3 transcripts in two different Shank3 mutant mouse lines (Shank3B and Shank3ΔC) having partial deletions of Shank3 exons. We validated an increase in Shank3 transcripts in the hippocampus, cortex, and striatum, but not in the cerebellum, of Shank3B heterozygous (HET) and KO mice, using qRT-PCR analyses. In particular, expression of the N-terminal exons 1–12, but not the more C-terminal exons 19–22, was observed to increase in Shank3B mice with deletion of exons 13–16. This suggests a selective compensatory activation of upstream Shank3 promoters. Furthermore, using domain-specific Shank3 antibodies, we confirmed that the increased Shank3 transcripts in Shank3B KO mice produced a small Shank3 isoform that was not detected in wild-type mice. Taken together, our results illustrate another layer of complexity in the regulation of Shank3 expression in the brain, which may also contribute to the phenotypic heterogeneity of different Shank3 KO mouse lines.